Mussel adhesive protein fused with VE‐cadherin extracellular domain promotes endothelial‐cell tight junctions and in vivo endothelization recovery of vascular stent. Issue 1 (11th April 2019) - Yang, Dongchuan; Yan, Wenhua; Qiu, Juhui; Huang, Yuhua; Li, Tianhan; Wang, Yi; Wang, Nan; Durkan, Colm; Huang, Junli; Yin, Tieying; Wang, Guixue
Abstract: Improving the surface properties of vascular stents to accelerate endothelialization in vivo could play an important role in minimizing the risk of late thrombosis. We previously showed that mussel adhesive protein fused with VE‐cadherin extracellular domain (VE‐M) specifically triggered endothelial cell adhesion in vitro . In this study, using stent implants coated with VE‐M, we evaluated the clinical applicability of VE‐M in endothelialization recovery in vivo . First, we explored the effect of VE‐M on hemocompatibility and tight junctions between endothelial cells (ECs) in vitro . VE‐M significantly inhibited platelet adhesion and promoted EC proliferation. Furthermore, VE‐M drastically increased the centralization of F‐actin in human umbilical vein endothelial cells (HUVECs) along the cell contacts, reduced fluorescein isothiocyanate (FITC)—dextran transport across the HUVECs, and elevated expression levels of tight junction proteins (TJPs) in ECs. We then evaluated the effect of VE‐M on endothelialization recovery in vivo through implantation of vascular stents. At 1 day after implantation, stents coated with VE‐M recruited more endothelial progenitor cells (EPCs) than bare stents. At 7 days after implantation, VE‐M stents had a greater coverage of ECs than bare stents. At 1 month after implantation, ECs on VE‐M stents were appropriately elliptical in morphology and closely resembled physiological morphology. Hematoxylin‐eosin (HE) staining revealed little in‐stent neointima formation on VE‐M stents, and SEM images revealed that smooth endothelium had formed on VE‐M stents without adherent platelets. Taken together, these findings indicate that VE‐M accelerates in vivo endothelialization of vascular stents via recruitment of EPCs and promotes endothelium formation and could be explored as a potential bioactive coating for vascular implant. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 108B:94–103, 2020.